2016
DOI: 10.1016/j.physleta.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and doping dependence of normal state spectral properties in a two-orbital model for ferropnictides

Abstract: Using a second-order perturbative Green's functions approach we determined the normal state spectral function A( k, ω) employing a minimal model for ferropnictides. Used before to study magnetic fluctuations and superconducting properties, it includes the two effective bands related to Fe-3d orbitals proposed by S. Raghu et al. [Phys. Rev. B 77, 220503 (R) (2008)], and local intra-and inter-orbital correlations for the effective orbitals. Here, we focus on the normal state electronic properties, in particula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…-We present magnetotransport results for the normal state of FeSe compounds, and compare them with those calculated as presented in the previous section. Using the optimal correlation value U = 3 eV, previously found to describe best other electronic properties of these compounds [12], we analize the dependence on temperature, doping and magnetic field H z = H, and compare our results with new experimental data and those of ref. [10], as well as with the results obtained assuming uncorrelated electrons.…”
Section: Calculation Of Magnetotransport Properties Of Fese Compounds -mentioning
confidence: 94%
See 4 more Smart Citations
“…-We present magnetotransport results for the normal state of FeSe compounds, and compare them with those calculated as presented in the previous section. Using the optimal correlation value U = 3 eV, previously found to describe best other electronic properties of these compounds [12], we analize the dependence on temperature, doping and magnetic field H z = H, and compare our results with new experimental data and those of ref. [10], as well as with the results obtained assuming uncorrelated electrons.…”
Section: Calculation Of Magnetotransport Properties Of Fese Compounds -mentioning
confidence: 94%
“…( 1). The effect of local intra-and inter-orbital correlations in ferropnictides was previously studied [12,19,22]. It was found that the inter-orbital correlation was less relevant than the intra-orbital one.…”
Section: Calculation Of Magnetotransport Properties Of Fese Compounds -mentioning
confidence: 99%
See 3 more Smart Citations